Perception and pattern of parental involvement in basic education provision in Ogun State, Nigeria. (2011)
This study examined the perception and pattern involvement in basic education at the junior secondary school level in Ogun State, Nigeria. Parents of one thousand three hundred and seventy-three (1373) students randomly selected through multisatge sampling procedure from thirty secondary schools participated in the study. A valid and reliable instrument, Parents' Perception and Pattern Involvement Qustionnnaire that was premissed on Epstein (1995) framework was used to obtain responses from the parents. Data was descriptively analysed using frequency counts, percentages and pie-charts. the findings indicated that the parents have good perception of their involvement in the provison of basic education for their wards but the pattern revealed that in practice, parents see provision of education as the sole responsibilty of the government. It was recommended that parents should not only have a positive perception but, rather, be actively and positively involved in the provision of education in the state. In addition, parent invovement in basic education can be enhanced through advocacy and education programmes.